Plant density and arrangement in sunflower - Silva, Paulo Regis Ferreira da; Rizzardi, Mauro Antônio; Trezzi, Michelangelo Müzell; de Almeida, Milton luiz (Pesquisa Agropecuaria Brasileira, 1995)
A serie of trials was conducted in order to evaluate the effect of factors such as cultivar, planting date, fertility level and weed control, which affect the sunflower crop response to plant density and arrangement. The trials were carried out at Eldorado do Sul and Passo Fundo, respectively in phisiographic regions of Depressão Central and Planalto Médio, in the state of Rio Grande do Sul, Brazil. The short season cultivars with low height enabled the utilization of higher plant density than long season cultivars with tall height. The short season cultivars with early planting date (late July) and more fertility in the soil provided higher densities. The grain yield did not vary with the utilization of distinct interrow spacings. Oil content of Contisol 711 cultivar increased with density enhancement. However, for all cultivars tested oil content didn't modify with change in plant arrangement. In weed infested areas, narrower spacings were more efficient to reduce competition.